Material particulado atmosférico da cidade de São Carlos e sua toxicidade em culturas de células pulmonares - Nascimento, Rita de Kássia Silva do (Universidade Federal de São Carlos, 2022)
PM air pollution is one of the principal causes of health problems in many regions’ world. This potential may be associated with the more than 500 compounds with toxic, mutagenic and carcinogenic effects already identified in PM that can originate from different natural and anthropogenic sources. Thus, the present study proposed to assess the chemical composition of PM10 from the city of São Carlos-SP and its toxicity in lung cells, tumor alveolar epithelial (A549), and non-tumor fibroblasts (MRC5). PM10 samples were collected for 24 h in 2016 and subjected to chemical analysis for the PAHs and their derivatives determination, in addition to analyzing saccharides and water-soluble ions to assist in the PM10 emission sources identification to the atmosphere. In vitro biological analyzes of cell viability, ROS, and cell proliferation were performed to evaluate the toxicity of PM10 extracts. The annual mean PM10 concentration was 21.12 ± 9.90 μg m-3, lower than that legislated limit in Brazil but higher than that recommended by the WHO. In these samples, the principal emission sources were: biomass burning with secondary aerosols, biomass burning and fossil fuels, biogenic aerosols, and soil. The risk to human health from exposure to PAHs estimated by BaPE was 3.09 ± 4.23 lung cancer cases per 100,000 people. Furthermore, biological analyzes identified a significant reduction in the viability of A549 and MRC5 cells, exposed to PM10 extracts for 72 h, and also the formation of ROS. In the face of these results, given the observed toxicological effects, it is concluded that more studies are needed with different cell lines and better control and reduction of PM emissions to the atmosphere.
Atmospheric particulate matter from the city of São Carlos and its toxicity in pulmonary cell cultures
Keywords: MP10; Toxicidade; Células pulmonares; PM10; Toxicity; Lung cells; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL